The Oscars in Twitter: insights acquired through social network analysis. (16th July 2021) - Vrana, Vasiliki; Kydros, Dimitrios
Twitter offers tremendous opportunities for people to engage in discussion regarding the Oscars awards through information sharing, expressing opinions, disappointment or enthusiasm on movies, casts, and productions. Despite the huge number of tweets generated and the notable excitement about the Oscars, there is a void in the literature about the dynamic interconnections of users interacting in Twitter. In this paper, we use social network analytic techniques to record and create networks of users discussing and interacting in Twitter around the search term 'Oscars'. We subsequently present and study the users' networks gaining insights regarding their clusterability in communities and some of their discussion topics. We also study the macroscopic structure of the users' network and prove that they belong to a class of networks bearing the scale-free topology. Finally, we create new networks based on the actual content of the tweets, based on word adjacencies and we proceed with a similar investigation on these semantic networks.